Examining the mediating effect of self-efficacy on the relationship between work experience, ICT acceptance and employability among undergraduate students in Nigerian universities - Wujema, Baba Kachalla; Mohd Rasdi, Roziah; Abu Samah, Bahaman; Abdullah, Abdul Lateef Krauss; Abdul Aziz, Mohd Faiq (Human Resource Management Academic Research Society, 2021)
The purpose of the study was to look into the relationship between work experience, ICT acceptance and employability among undergraduate students in North Eastern universities in Nigeria. The study also examines the mediating effect of self-efficacy among undergraduate students. The research sample was 264 which was also drawn among undergraduate students in North Eastern Nigeria. The result showed that work experience does not have a significant relationship with employability among undergraduate students in the universities. Likewise, ICT acceptance was shown to have a significant relationship with employability among undergraduate students in the universities. The results further showed that, both ICT acceptance and work experience have a significant relationship with self-efficacy and employability among undergraduate students in the universities. However, self-efficacy was found to mediate the relationship between ICT acceptance and employability among undergraduate students in the universities. Additionally, self-efficacy was found to have an indirect effect on the relationship between work experience and employability among undergraduate students in the universities. This study contributes to the body of knowledge since employability among undergraduate students in the region was under researched, consequently undertaking this study has shown a limelight to researches in the region.